The Digitalization of ZIS Services from a Maqashid Shariah Perspective - Surur, Miftahus; Hafidz Al Fajar, Adam; Gunawan, Gunawan; Rahmi Irfaniah, Nur; Purnawan, Puji (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study aims to explore two main issues: (1) how the values of maqashid sharia can be integrated into the digitalization of Zakat, Infaq, and Sadaqah (ZIS) services, and (2) how the digitalization of ZIS services impacts social empowerment in the digital era. The advancement of information technology has encouraged zakat management institutions to adopt digital systems for collecting and distributing ZIS funds. However, it is essential to ensure that these innovations remain grounded in core sharia principles that emphasize justice, transparency, and social sustainability. This research employs a library research method with a descriptive-analytical and comparative approach. Data were collected from national and international scholarly journals accessed through databases such as Google Scholar, DOAJ, SINTA, and Scopus, using keywords such as “digital zakat,” “maqashid sharia,” “social empowerment,” and “technology-based zakat.” The relevant literature was analyzed to identify patterns of maqashid integration and to evaluate the social impact of ZIS digitalization. The findings reveal that the digitalization of ZIS has actualized maqashid sharia principles through various digital features, including online zakat education (hifz al-din), humanitarian aid via digital platforms (hifz al-nafs), transparent fund management (hifz al-mal), and Islamic financial digital literacy (hifz al-‘aql). Furthermore, digitalization has been proven to enhance social empowerment through improved efficiency in distribution, broader access, and sustainable economic strengthening of the beneficiaries (mustahik).